1998
DOI: 10.1128/aac.42.5.1249
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of grlA , grlB , gyrA , and gyrB Mutations in 116 Unrelated Isolates of Staphylococcus aureus and Effects of Mutations on Ciprofloxacin MIC

Abstract: One hundred sixteen unrelated clinical isolates ofStaphylococcus aureus (70 ciprofloxacin resistant and 46 ciprofloxacin susceptible) from eight countries were studied for the presence of mutations in the grlA, grlB,gyrA, and gyrB gene loci. Two mutations withingrlA (located at codons 80 and 84) and two mutations withingyrA (located at codons 84 and 88) were clearly associated with ciprofloxacin resistance, although other mutations detected within the four genes studied may also contribute to decreased suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(64 citation statements)
references
References 20 publications
6
54
1
Order By: Relevance
“…Most striking has been the rapid emergence of a high prevalence of quinolone resistance (190%) among methicillinresistant but not methicillin-susceptible strains of S. aureus in many parts of the world [88,89]. This same difference in prevalence of quinolone resistance also exists between methicillinresistant and -susceptible strains of coagulase-negative staphylococci [90].…”
Section: Bacterial Resistance Associated With Use Of Quinolonesmentioning
confidence: 89%
“…Most striking has been the rapid emergence of a high prevalence of quinolone resistance (190%) among methicillinresistant but not methicillin-susceptible strains of S. aureus in many parts of the world [88,89]. This same difference in prevalence of quinolone resistance also exists between methicillinresistant and -susceptible strains of coagulase-negative staphylococci [90].…”
Section: Bacterial Resistance Associated With Use Of Quinolonesmentioning
confidence: 89%
“…For example, amino acid in parE changes from Pro25 → His, Glu422 → Asp, Lys441 → Ile, Lys428 → Gln, Asp494 → Asn, Lys428→ Gln, Gly442 → Ser, Asp432 → Asn or Gly, Pro451 → Ser or Gln and Asn470 → Asp among fluoroquinolone-resistant S. aureus, (Schmitz et al, 1998;Ince & Hooper, 2001;Fournier & Hooper, 1998). However, these mutations may not be directly responsible for high-level resistance but rather increase the resistance levels in isolates already harboring two gyrA mutations and one parC mutation.…”
Section: Discussionmentioning
confidence: 99%
“…14 The occurrence of low-level resistance against fluoroquinolones after a single mutation in parC has been described earlier for Enterococcus faecalis, S. aureus, and S. pneumoniae, whereas high-level resistant isolates had mutations in both parC and gyrA. 8,20,30,34 In M. bovirhinis, however, a single mutation in parC (position 80) resulted in different MIC profiles, including low-and high-level resistant isolates. 16 The authors suggested that the differences in MIC might have been caused by the level of expression of the quinolone efflux transporter.…”
Section: Mic (G/ml)mentioning
confidence: 90%